Effect of different reaction parameters on the lipase-catalyzed selective acylation of polyhydroxylated natural compounds in ionic liquids - Katsoura, M. H.; Polydera, A. C.; Katapodis, P.; Kolisis, F. N.; Stamatis, H. (2007)
The effect of various reaction parameters on the enzymatic acylation of plant polyhydroxylated compounds, including phenolic and flavonoid glucosides (salicin, helicin, esculin and naringin), was investigated in imidazolium-based ionic liquids (1-butyl-3-methylimidazolium tetrafluoroborate [bmim]BF4 and 1-butyl-3-methylimidazolium hexafluorophosphate [bmim]PF6), using immobilized lipase B from Candida antarctica. The conversion yield, the regioselectivity and the reaction rate of the biocatalytic process strongly depended on the ionic liquid used, their water content, the incubation temperature, as well as the solubility and the concentration of substrates. For most glucosides tested, one major product (monoacylated derivative) was detected as a result of the acylation of the primary hydroxyl group of glucose moiety. The acylation rate and the regioselectivity of the process are higher in [bmim]BF4, where the solubility of all glucosides is significantly higher than in [bmim]PF6 or acetone. Response surface methodology (RSM) based on a five level-three variable central composite circumscribed design, was employed to evaluate the interactive effect of the molar ratio of substrates (MR), the initial concentration of glucoside (N) and the reaction time (RT), as well as for their optimization in [bmim]BF4. At the optimal reaction conditions the maximum acylation yield was 87%. The amount of monoacylated derivatives produced in a single-step biocatalytic process reached values up to 31.6 g/l which is considerably higher than those reported for organic media. (c) 2007 Published by Elsevier Ltd. Process Biochemistry